Weight gain and menstrual abnormalities between users of Depo-provera and Noristerat - Oshodi, Yusuf Abisowo; Agbara, Joy Oyinyechi; Ade fashola, Olamide O.; Akinlusi, Fatimat Motunrayo; Olalere, Haleema Folasade; Kuye, Taiwo O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Progesterone only injectable contraceptive provides long acting contraception against unwanted pregnancy. Alterations in menstrual pattern are a well known side effect of this effective contraceptive method. Objective of this study was to compare the weight gain and pattern of menstrual abnormalities in users of Depot Medroxyprogesterone Acetate (DMPA) and Norethisterone Enanthate (Noristerat) in LASUTH. Methods: Retrospective comparative study conducted over a 3year period (January 2013 to December 2015) and involving 237 subjects who used injectable hormonal contraceptive (either DMPA or Noristerat). Case records of all the subjects were retrieved and information obtained on socio-demographic data, parity, previous contraceptive method and reason for discontinuation within one year of usage. Other information including subjects’ weight, menstrual cycle length and pattern, and side effects were collected at 3, 6 and 12 months for DMPA group and 2, 4 and 12 months interval for Noristerat group. Data obtained were analyzed using statistical packages for social sciences (version 19). Results: The combined mean age was 34.15±1.36 years. The mean weight at commencement was 68.16kg for DMPA and 66.61kg for Noristerat users while after a year, it significantly increased to 71.27kg for DMPA and 69.07kg for Noristerat users (P<0.05). No change in menstrual pattern was noted in 10% of DMPA and 7% of Noristerat users while 60% of DMPA and 57% of Noristerat had amenorrhoea by the end one year period. Five percent each of DMPA and Noristerat users perceived weight gain as problem significant enough to discontinue both methods respectively. Overall, 24% of DMPA and 19.1% of Noristerat users discontinued use after one year. Conclusions: There were significant weight gain between users of DMPA and Noristerat which was not considered a problem. Amenorrhoea was the commonest menstrual abnormality responsible for discontinuation of either method.